Compressive Strength Of Reactive Powder Concrete Containing Bamboo Leaf Ash - Yulius Rief Alkhaly Alkhaly (Faculty of Engineering, Malikussaleh University, 2018)
The development of reactive powder concrete as an ultra-high-performance-concrete construction material in Indonesia has a very high prospect, mainly due to the availability of local raw materials. The original RPC composition developed in the 1990s consists of Portland cement, silica fume, silica sand, quartz powder (optional), and micro steel fibers (optional). This research is an initial study of the use of bamboo leaf ash as silica fume substitution to produce RPC with local Indonesian material. In this study, RPC mixture was manufactured base on the existing of previous research. Synthesized bamboo leaf ash (SBLA) was utilized to replace 100% of silica fume content in the mix. The experimental results confirmed that replacing of all silica fume volume in the mix with SBLA is promising to be applied as pozzolanic material to produce RPC. In this study, The RPC mixture containing 25% SBLA of cement mass was able to maintain a 73.84% compressive strength of the control mix. Furthermore, a mean compressive strength of plain RPC of 63.87 MPa was developed using at 28th days standard curing with low cement content.